Characters Design of Public Service Advertisement Posters to Increase Interest in Learning Javanese for Elementary School Children in Kendal Regency - Afriyani, Wahyu Eka; Senoprabowo, Abi (Universitas Nusantara PGRI Kediri, 2025)
In Kendal Regency, elementary school students' interest in learning Javanese has declined, as evidenced by the fact that 39.7% of students have not yet mastered the subject. Students have expressed that they prefer learning with visual representations rather than just theory from textbooks. Therefore, this Public Service Advertisement (PSA) poster design aims to increase students' interest in learning Javanese by integrating visual elements and relevant learning material. The data collection methods used in this design include interviews and questionnaires for primary data, and observations and literature reviews for secondary data. The analysis in this design is conducted using the 5W+1H approach, along with the five-stage design method by Robin Landa. This poster features Javanese cultural materials in line with the Javanese curriculum for elementary schools, including topics such as wayang, traditional Javanese houses, tembang macapat, Javanese traditional dance, and Javanese script. It is expected that this poster can be optimally used according to its function to increase students' interest in learning Javanese at the elementary school level in Kendal Regency.